HUBUNGAN ASUPAN PROTEIN,SERAT DAN DURASI TIDUR DENGAN STATUS GIZI MAHASISWA S-1 ILMU GIZI UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA - Dini Rachmadianti, (2020)
Nutritional status is a measure of the condition of an individual's body that can be seen from the food consumed and the use of substances in the body. Many aspects affect the nutritional status of adolescents, such as heredity, lifestyle and environment. Eating habits and lifestyle can affect the amount of food consumption and nutrient intake. The purpose of this study was to determine the relationship between protein intake, fiber and sleep duration with nutritional status of S-1 nutrition student UPN Veteran Jakarta. This study using a cross sectional design with stratified random sampling technique. The population in this study were all undergraduate students of Nutrition Science class of 2017 and 2018. Samples taken were 46 respondents. Analysis of the data used is the Chi-Square test. The results showed that there was no relationship between protein intake (p = 1.000), fiber (p = 0,239) and sleep duration (p = 1.000), with nutritional status of S-1 nutrition student UPN Veteran Jakarta